Genome-wide identification of dysregulated alternative splicing and RNA-binding proteins involved in atopic dermatitis - Yang, Yaqi; Chen, Hao; Jiang, Qing; Yang, Lin; Zhu, Rongfei; Huang, Nan (Frontiers in Genetics, 2024)
Objectives: We explored the role and molecular mechanisms of RNAbinding proteins (RBPs) and their regulated alternative splicing events (RASEs) in the pathogenesis of atopic dermatitis (AD). Methods: We downloaded RNA-seq data (GSE121212) from 10 healthy control skin samples (healthy, Ctrl), 10 non-lesional skin samples with AD damage (non-lesional, NL), and 10 lesional skin samples with AD damage (lesional, LS). We performed the analysis of differentially expressed genes (DEGs), differentially expressed RBPs (DE-RBPs), alternative splicing (AS), functional enrichment, co-expression of RBPs and RASEs, and quantitative polymerase chain reaction (qPCR). Results: We identified 60 DE-RBP genes by intersecting 2141 RBP genes from existing reports with overall 2697 DEGs. Most of the DE-RBP genes were found to be upregulated in the AD LS group, and related to immune and apoptosis pathways. We observed different ASEs and RASEs among the healthy, AD NL, and AD LS groups. In particular, alt3p and alt5p were the main ASEs and RASEs in AD NL and AD LS groups, compared to the healthy group. Furthermore, we constructed co-expression networks of DE-RBPs and RAS, with particular enrichment in biological pathways including cytoskeleton organization, inflammation, and immunity. Subsequently, we selected 7 genes that are commonly present in these 3 pathways to assess their expression levels in the peripheral blood mononuclear cells (PBMCs) from both healthy individuals and AD patients. The results demonstrated up-regulation of 4 genes (IFI16, S100A9, PKM, and ENO1) in PBMCs of AD patients, which is highly consistent with DE-RBPs genes analysis. Finally, we selected 4 RAS genes regulated by RBPs that related to immune pathways and examined their RASEs in PBMCs from both AD patients and healthy controls. The results revealed an increased percentage of RASEs in the DDX60 gene in AD, which is highly consistent with AS analysis. Conclusion: Dysregulated RBPs and their associated RASEs may have a significant regulatory role in the development of AD and could be potential therapeutic targets in the future.